E-commerce – trends and development opportunities - Radziszewska, Aleksandra (Management and Administration Journal, 2019)
The paper describes the tools of marketing communication with e-customers and trends concerning e-commerce. Special attention has been paid to personalization and recommender systems. The paper treats the characteristics of consumer behaviours on the business-to-customer market and the main barriers in customer relationship management. In this context the relationship with e-customers and the tools of marketing communication in electronic customer relationship have been described. The rapid growth of e-commerce has created product overload where customers on the Web are no longer able to effectively choose the products they are exposed to. There is a lot of imperfect information and a large supply available for consumers, and so it is extremely difficult to identify their own needs and preferences and ways for satisfying them. Recommendations are a type of communication and an especially important issue in e-marketing. It is easy to find many websites where a customer needs advice before taking the decision to purchase a product. Therefore, recommendations are a powerful tool to assist customers in these decisions. The paper refers to the challenges resulting from the growing importance of network and virtual communities, where the consumer is perceived as a value co-creator.